Pelatihan Implementasi Konseling Karier Model KIPAS bagi Guru BK Se-Kota Palangka Raya: Training on the Implementation of KIPAS Model Career Counseling for Guidance and Guidance Teachers throughout the City of Palangka Raya - Sendayu, Fendahapsari Singgih; Romiaty, Romiaty; Nonsihai, Nonsihai; Feronika, Nopi; Ginting, Herda Fitri Br (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The competence of High School Guidance and Counseling Teachers (SMA BK Teachers) is very important to be improved in facing the challenges of the era of revolution 4.0. Improving the competence of High School Guidance and Counseling Teachers is expected to be able to help students think analytically, evaluatively, creatively, and complexly known as High Order Thinking Skills (HOTs), and develop students' career readiness. Therefore, high school guidance and counseling teachers must have creative and innovative strategies for providing career counseling services. This creative and innovative form can be seen in the design of a career counseling service model with group counseling services that are oriented towards developing 21st-century skills, namely critical thinking skills, creative thinking skills, collaboration skills, and communication skills by implementing the KIPAS counseling model. The method used in the KIPAS model career counseling training through this group counseling service is to apply a training model with an "in-on-in" pattern, namely three activities including one synchronous offline activity, one asynchronous online activity, and one assignment activity. The number of participants was 30 high school guidance and counseling teachers in Palangka Raya City with a pattern of 42 lesson hours and was carried out for four weeks. This training has succeeded in increasing the insight and competence of high school guidance and counseling teachers to practice the KIPAS model of career counseling services sequentially according to the KIPAS counseling stages.